Pengaruh Organisme Perifiton dalam Memperbaiki Kualitas Air pada Lahan Basah Buatan Sistem Aliran Air Permukaan Bebas - Syamsul Bahri; Iga Maliga (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2018)
The main removal mechanism of water contaminants in wetlands is microorganisms activities. One of them is a periphyton that lives on a submerged substratum. Therefore, a study of the influence of periphyton in construcetd wetlands which is important in improving water quality. The research objectives were to identify of the quality of influent, the composition of algae, the periphytone algae as primary producer, the influence of free water surface velocity factor, the quality of effluent, efectivity and eficiency of constracted wetlands. The study was conducted in Bandung City on January 2017. The results show that influent of sewage is contaminated with domestic wastewater. In constructed wetlands foundthree classes of benthic algae as periphyton, namely Bacillariophyta, Chlorophyta, and Cyanophyta. Periphyton algae play an important role in the transfer of oxygen into water colomn. The free surface velocity factor was strongly correlated to the percent removal of nitrate (r = 0.84) and very strong to the percent removal of total phosphate (r = 0.90) by periphyton. The quality of effluent that qualified grade III were total phosphate and COD parameter only. Effectivity of treatement were 6,6% ? 38,3% BOD, 6,0% ? 38% COD. Efficiency of treatment on the water discharge 0,01 L/s were 4,4% ammonium; 39,2% nitrat; 47,1% organic nitrogen; 53,6% phosphate total; 38,3% BOD; 38% COD; 76,5% detergent.